Triclonal gammopathy in a patient with smoldering Plasma Cell Myeloma (PCM)* - Myrlande Maingrette; Vikram Palamalai (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2021)
Objective: Triclonal gammopathies, although considered a variant of monoclonal gammopathy of unknown significance, have been shown to be associated with other malignancies and inflammatory pathologies.  There is sadly a paucity of triclonal gammopathies reported in the literature. Here, we present a case diagnosed with triclonal gammopathy/ MGUS to add to the small body of knowledge available about this rare condition. Methods: Review of the case history and laboratory investigations. Results: The case history and progression of disease of an 86 year old female diagnosed with triclonal gammopathy/ MGUS (by capillary electrophoresis and immunosubtraction), smoldering plasma cell myeloma, progressive paraproteinemia and worsening renal and hepatic functions and yet no detected bone marrow plasma cell clonality is described with relevant clinical investigations. Conclusion: Given the rarity of triclonal gammopathies, currently available research has yet to establish whether they arise from one clone or three unrelated clones of immunoglobulins.   We discussed a case of triclonal gammopathy without any detected bone marrow plasma cell clonality. Increased awareness of this disorder and its associated analytical  difficulties can help in the formulation of future guidelines for their analysis and treatment,  as  more cases are catalogued.